Disruption in Thyroid Signaling Pathway: A Mechanism for the Effect of Endocrine-Disrupting Chemicals on Child Neurodevelopment - Ghassabian, Akhgar; Trasande, Leonardo (Frontiers in Endocrinology, 2018)
Thyroid hormones are crucial in normal brain development. Transient and mild thyroid hormone insufficiency in pregnancy is also associated with impaired neurodevelopment in the offspring (e.g., 3-4 IQ score loss in association with maternal free thyroxine in the lowest 5th percentile). While inadequate iodine intake remains the most common underlying cause of mild thyroid hormone insufficiency in vulnerable populations including pregnant women, other factors such as exposure to environmental contaminants have recently attracted increasing attention, in particular in interaction with iodine deficiency. Endocrine disrupting chemicals (EDCs) are natural and synthetic substances with ubiquitous exposure in children and adults including pregnant women. EDCs interfere, temporarily or permanently, with hormonal signaling pathways in the endocrine system by binding to hormone receptors and modifying gene expression. Other mechanisms involve alterations in production, metabolism, and transfer of hormones. Experimental studies have shown that exposures to EDCs affect various brain processes such as neurogenesis, neural differentiation and migration, as well as neural connectivity. Neuroimaging studies confirm brain morphological abnormalities (e.g., cortical thinning) consistent with neurodevelopmental impairments as a result of EDC exposures at standard use levels. In this review, we provide an overview of present findings from toxicological and human studies on the anti-thyroid effect of EDCs with a specific attention to fetal and early childhood exposure. This brief overview highlights the need for additional multidisciplinary studies with a focus on thyroid disruption as an underlying mechanism for developmental neurotoxicity of EDC, which can provide insight into modifiable risk factors of developmental delays in children.